2020
DOI: 10.1111/bcp.14215
|View full text |Cite
|
Sign up to set email alerts
|

Do anti‐tumour necrosis factor‐α biologics affect subclinical measures of atherosclerosis and arteriosclerosis? A systematic review

Abstract: Aims: Inflammatory cytokines, particularly tumour necrosis factor-α (TNFα), are thought to promote arterial disease through a variety of mechanisms leading to arteriosclerosis and atherosclerosis. We reviewed the existing evidence of the effect of anti-TNFα treatment on arteriosclerosis and atherosclerosis in chronic inflammatory disease. Methods:We performed a systematic review of studies examining effects of monoclonal antibodies against TNFα on subclinical measures of arteriosclerosis (arterial pulse wave v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 85 publications
(78 reference statements)
0
10
0
1
Order By: Relevance
“…Tumor necrosis factor-α inhibitors (adalimumab, certolizumab, etanercept, or infliximab) showed a protective cardiovascular profile in multiple, mainly observational studies of psoriasis. It has been hypothesized that this action is probably mediated by their beneficial effect on endothelial cell function (66). There is at present no strong, definite evidence for a significant beneficial effect of anti-TNF-α biologics on endothelial function in psoriasis (66,67), although some promising data do exist.…”
Section: Tumor Necrosis Factor-α Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor necrosis factor-α inhibitors (adalimumab, certolizumab, etanercept, or infliximab) showed a protective cardiovascular profile in multiple, mainly observational studies of psoriasis. It has been hypothesized that this action is probably mediated by their beneficial effect on endothelial cell function (66). There is at present no strong, definite evidence for a significant beneficial effect of anti-TNF-α biologics on endothelial function in psoriasis (66,67), although some promising data do exist.…”
Section: Tumor Necrosis Factor-α Inhibitorsmentioning
confidence: 99%
“…It has been hypothesized that this action is probably mediated by their beneficial effect on endothelial cell function (66). There is at present no strong, definite evidence for a significant beneficial effect of anti-TNF-α biologics on endothelial function in psoriasis (66,67), although some promising data do exist. TNF-α blockade has led to improvement of vascular function assessed through resting endothelium-dependent vascular tone by low-flow-mediated constriction, yet FMD values remained unchanged (68).…”
Section: Tumor Necrosis Factor-α Inhibitorsmentioning
confidence: 99%
“…Предполагали, что необходимо устранить избыток ФНО-α в организме, подавить хроническое воспаление сосудистой стенки, и победа будет достигнута. Однако эксперименты с ингибированием ФНО-α разочаровали: атерогенез усиливался [36]. Возможно, статины, аспирин, метотрексат, колхицин обладают иммуномодулирующим эффектом и оказывают антиатерогенный эффект, подавляя в какой-то степени хроническое воспаление [32].…”
Section: воспаления в ракunclassified
“…Anti-TNF- α therapy also has a favorable effect on the improvement of arterial stiffness, measured by the gold standard aortic pulse wave velocity (aPWV), in patients with psoriatic arthritis ( Angel et al, 2010 ). Despite that a recent systematic review showed no significant effect of TNF- α inhibitors on the subclinical indicators of atherosclerosis in inflammatory diseases including psoriasis, a positive effect of TNF- α biologics on the clinical outcomes of CVDs via alternate pathways, such as primary disease remission or reduced prothrombotic tendency, cannot be ruled out ( Knowles et al, 2020 ).…”
Section: Manuscript Formattingmentioning
confidence: 99%